Dietary Wolfberry Supplementation Enhances the Protective Effect of Flu Vaccine against Influenza Challenge in Aged Mice. Issue 2 (11th December 2013) - Du, Xiaogang; Wang, Junpeng; Niu, Xinli; Smith, Donald; Wu, Dayong; Meydani, Simin Nikbin
Abstract: Current vaccines for influenza do not fully protect the aged against influenza infection. Although wolfberry (goji berry) has been shown to improve immune response, including enhanced antibody production, after vaccination in the aged, it is not known if this effect would translate to better protection after influenza infection, nor is its underlying mechanism well understood. To address these issues, we conducted a study using a 2 × 2 design in which aged male mice (20–22 mo) were fed a control or a 5% wolfberry diet for 30 d, then immunized with an influenza vaccine or saline (control) on days 31 and 52 of the dietary intervention, and finally challenged with influenza A/Puerto Rico/8/34 virus. Mice fed wolfberry had higher influenza antibody titers and improved symptoms (less postinfection weight loss) compared with the mice treated by vaccine alone. Furthermore, an in vitro mechanistic study showed that wolfberry supplementation enhanced maturation and activity of antigen-presenting dendritic cells (DCs) in aged mice, as indicated by phenotypic change in expression of DC activation markers major histocompatibility complex class II, cluster of differentiation (CD) 40, CD80, and CD86, and functional change in DC production of cytokines interleukin-12 and tumor necrosis factor-α as well as DC endocytosis. Also, adoptive transfer of wolfberry-treated bone marrow DCs (loaded with ovalbumin323–339 -peptide) promoted antigen-specific T cell proliferation as well as interleukin-4 and interferon-γ production in CD4 + T cells. In summary, our data indicate that dietary wolfberry enhances the efficacy of influenza vaccination, resulting in better host protection to prevent subsequent influenza infection; this effect may be partly attributed to improved DC function.